Art Forum Berlin 1997. - Büttner, Claudia; Grasskamp, Walter; Stepken, Angelika; Art Forum Berlin 1997 (Berlin : European Galleries - Projektgesellschaft mbH Berlin, 1997)
Abakanowicz, Magdalena ; Ahtila, Eija-Liisa ; Appel, Karel ; Appelt, Siegrun ; Araki, Nobuyoshi ; Armajani, Siah ; Arman ; Armleder, John M ; Art & Language ; Artschwager, Richard ; Asker, Curt ; Assig, Martin ; Atelier van Lieshout ; Badiola, Txomin ; Baldessari, John ; Balka, Miroslaw ; Balkenhol, Stephan ; Ballester, José Manuel ; Barth, Uta ; Baselitz, Georg ; Baumgartner, Franz ; Blumenfeld, Erwin ; Boll, Otto ; Bourgeois, Louise ; Broodthaers, Marcel ; Brower, Steven ; Burchill/McCamley ; Burmester, Gerardo ; Bustamante, Jean-Marc ; Canogar, Daniel ; Cardiff, Janet ; Chamberlain, John ; Chevrier, Claire ; Collishaw, Mat ; Collyer, Robin ; Couturier, Stéphane ; Davids, Yael ; Davis, Christine ; Delaunay, Robert ; Dellbrügge & De Moll ; Denda, Elke ; Dion, Mark ; Ebersbach, Hartwig ; Etter, Ueli ; Feher, Laszlo ; Feng Mengbo ; Filippov, Andrej ; Fischer, Roland ; Riverhead (New York) ; Flemming, Alex ; Fleury, Sylvie ; Franke, Manuel ; Fricke, Adib ; Friedl, Peter ; Fulton, Hamish ; Gastinti, Marco ; Geier, Helmut ; Geiger, Marcus ; Gerritz, Frank ; Gilbert & George ; Gjerdevik, Nils Erik ; Gordon, Douglas ; Gormley, Antony ; Grosse, Katharina ; Grünfeld, Thomas ; Haaning, Jens ; Hakansson, Henrik ; Heizer, Michael ; Hemmert, Hans ; Hernandez, Anthony ; Herrera, José ; Hildebrand, Volker ; Hirschhorn, Thomas ; Höckelmann, Antonius ; Hödicke, Karl Horst ; Höfer, Candida ; Hoffmann, Leni ; Huber, Stephan ; Hüppi, Alfonso ; Illana, Fernando ; Immendorff, Jörg ; Jacobi, Frans ; Janicki, Alexander ; Jaros, Piotr ; Jones, Sarah ; Jouve, Valérie ; Judd, Donald ; Kaeseberg ; Kahrs, Johannes ; Kassak, Lajos ; Kern, Stefan ; Koester, Joachim ; Kogler, Peter ; Kounellis, Jannis ; Kreuter, Delphine ; Kuitca, Guillermo ; Kwon, Sowon ; Lago, Darren ; etc.
Duits
Duits & Engels
Engels
Art Forum Berlin 1997, 31.10 - 4.11.1997
boek